COVID-19 exposure and depression-anxiety levels among Saudi adults in the Jazan region: a study with a predominantly female and undergraduate sample - Busili, Amani; Makrami, Azizah; Keni, Amnah; Khardily, Alaa; Alzahrani, Dalyah; Busaily, Idris; Busayli, Fatimah (Frontiers in Psychiatry, 2023)
The COVID-19 pandemic has had far-reaching effects on global mental health, with studies consistently reporting high levels of depression and anxiety. However, limited research has explored the mental health situation following the pandemic and its association with COVID-19 exposure in the Jazan region, Saudi Arabia. A convenience sample of 377 participants, predominantly female (85.4%), with undergraduate education (74.5%), participated in this study. Data collection took place using a self-administered questionnaire between 1st August and 8th September 2022. The questionnaire covered demographic characteristics, COVID-19 exposure, depression assessment using the Patient Health Questionnaire-9 (PHQ-9), and anxiety evaluation through the Generalized Anxiety Disorders-7 (GAD-7). The mean age of the participants was 30.97 years (SD = 9.072). On average, the participants reported a moderate level of COVID-19 exposure (mean = 2.98, SD = 1.48). The mean depression score was 7.83 (SD = 6.43), with 20% experiencing moderate to severe depression. Similarly, the mean anxiety score was 6.75 (SD = 6.57), and 26% reported moderate to severe anxiety. Notably, participants with different COVID-19 exposure levels displayed significant differences in mean depression and anxiety scores (p = 0.001). Regression analysis indicated that anxiety levels significantly predicted depression (p < 0.001). Participants with high anxiety levels (≥ 10) also showed significantly higher depression scores compared to those with lower anxiety levels. Furthermore, demographic factors, such as student or unemployment status (p < 0.001), increased age (≥ 35) (p = 0.049), female gender (p = 0.009), unmarried/divorced/widowed marital status (p = 0.004), low monthly income (p = 0.019), and elevated depression levels (p < 0.001) were significant predictors of anxiety. These findings underscore the significant prevalence of depression and anxiety among the participants, with higher COVID-19 exposure correlating with increased scores for both. The study highlights the critical role of anxiety as a predictor of depression. Moreover, demographic factors played a significant role in influencing anxiety levels. Consequently, targeted mental health interventions are needed to address the psychological impact of COVID-19 exposure and effectively support those affected in the Jazan region, Saudi Arabia.